1979
DOI: 10.1111/j.1745-4557.1979.tb00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long‐term Storage on Quality of Processed Foods

Abstract: Experiments were conducted on the effects of long-term storage at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Salunkhe et al . (1979) evaluated the color of pineapple preserves filled in flexible retortable pouches during storage at 4.4, 21.1 and 37.8C.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Salunkhe et al . (1979) evaluated the color of pineapple preserves filled in flexible retortable pouches during storage at 4.4, 21.1 and 37.8C.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study are in agreement with the other findings on color change procedure of fruit preserves during storage at different temperatures. Salunkhe et al (1979) evaluated the color of pineapple preserves filled in flexible retortable pouches during storage at 4.4, 21.1 and 37.8C. They found that increasing temperature could accelerate color changes in samples and decrease the shelf life of products, respectively.…”
Section: Color Changes During Storagementioning
confidence: 99%
See 2 more Smart Citations